Further Progress in Functional Interlayers with Controlled Mechanical Properties Designed for Glass Fiber/Polyester Composites - Knob, Antonín; Lukeš, Jaroslav; Čech, Vladimír; Drzal, Lawrence (MDPI, 2018)
Compatible interlayers must be coated on reinforcing fibers to ensure effective stress transfer from the polymer matrix to the fiber in high-performance polymer composites. The mechanical properties of the interlayer, and its interfacial adhesion on both interfaces with the fiber and polymer matrix are among the key parameters that control the performance of polymer composite through the interphase region. Plasma-synthesized interlayers, in the form of variable materials from polymer-like to glass-like films with a Young’s modulus of 10–52 GPa, were deposited on unsized glass fibers used as reinforcements in glass fiber/polyester composites. Modulus Mapping (dynamic nanoindentation testing) was successfully used to examine the mechanical properties across the interphase region on cross-sections of the model composite in order to distinguish the fiber, the interlayer, and the modified and bulk polymer matrix. The interfacial shear strength for plasma-coated fibers in glass fiber/polyester composites, determined from the microindentation test, was up to 36% higher than those of commercially sized fibers. The effects of fiber pretreatment, single and double interlayers, and post-treatment of the interlayer on interfacial shear strength were also discussed. Functional interlayers with high shear yield strength and controlled physicochemical properties are promising for high-performance polymer composites with a controlled interphase.

Compatible interlayers must be coated on reinforcing fibers to ensure effective stress transfer from the polymer matrix to the fiber in high-performance polymer composites. The mechanical properties of the interlayer, and its interfacial adhesion on both interfaces with the fiber and polymer matrix are among the key parameters that control the performance of polymer composite through the interphase region. Plasma-synthesized interlayers, in the form of variable materials from polymer-like to glass-like films with a Young’s modulus of 10–52 GPa, were deposited on unsized glass fibers used as reinforcements in glass fiber/polyester composites. Modulus Mapping (dynamic nanoindentation testing) was successfully used to examine the mechanical properties across the interphase region on cross-sections of the model composite in order to distinguish the fiber, the interlayer, and the modified and bulk polymer matrix. The interfacial shear strength for plasma-coated fibers in glass fiber/polyester composites, determined from the microindentation test, was up to 36% higher than those of commercially sized fibers. The effects of fiber pretreatment, single and double interlayers, and post-treatment of the interlayer on interfacial shear strength were also discussed. Functional interlayers with high shear yield strength and controlled physicochemical properties are promising for high-performance polymer composites with a controlled interphase.
Further Progress in Functional Interlayers with Controlled Mechanical Properties Designed for Glass Fiber/Polyester Composites
Keywords: glass fiber; polymer-matrix composites; interface/interphase; nanoindentation; mechanical properties; microindentation test; glass fiber; polymer-matrix composites; interface/interphase; nanoindentation; mechanical properties; microindentation test